2022
DOI: 10.3390/app12052691
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Empirical Study for Prediction of Blast Loads

Abstract: This paper presents the issue of determining the blast load on an engineering structure. In cases of industrial accidents or terrorist attacks, in many cases it is necessary to determine the necessary explosion parameters to determine the response of the structure, preferably in a simple and time-saving manner. In such a way, the empirical relationships can be used to estimate the selected parameters of the explosion load. Many empirical relationships have been derived in the past, but not all are suitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the positive phase duration and the positive phase impulse given by K&B data are linearly dependent on and, consequently, at a given scaled distance , they differ by a factor for two different explosive loads with equivalent masses of and of TNT, respectively. According to [ 6 ], the accuracy of K&B data is questionable for scaled distances smaller than 2 m/kg 1/3 , and other reference data may be more accurate to estimate blast wave descriptors when, e.g., Semtex explosives are involved [ 8 ]. Keeping in mind these limitations, we derive from K&B data in the next sections the bandwidth of pressure sensors required to estimate the overpressure magnitude at the front of a blast wave, in order to achieve a desired estimation accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the positive phase duration and the positive phase impulse given by K&B data are linearly dependent on and, consequently, at a given scaled distance , they differ by a factor for two different explosive loads with equivalent masses of and of TNT, respectively. According to [ 6 ], the accuracy of K&B data is questionable for scaled distances smaller than 2 m/kg 1/3 , and other reference data may be more accurate to estimate blast wave descriptors when, e.g., Semtex explosives are involved [ 8 ]. Keeping in mind these limitations, we derive from K&B data in the next sections the bandwidth of pressure sensors required to estimate the overpressure magnitude at the front of a blast wave, in order to achieve a desired estimation accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…During an explosion, the measurement of the overpressure at the front of the generated blast wave by using pressure sensors is a standard and well-controlled technique (see, e.g., [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]). Assessing the magnitude of the overpressure peak is crucial to characterize explosives, because this magnitude can be used to derive a plethora of physical quantities at the blast wave front from the Rankine–Hugoniot relationships [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peak overpressure, labeled as Pso, is reached at this juncture. Following this, the pressure decreases exponentially until it returns to ambient levels at tA+to, where to signify the positive phase duration [20]. The study focused on non-contact, unconfined external explosions, shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-blast design of buildings should first obtain blast loads of buildings, in the past, scholars pay more attention to spherical charges 4 , 5 and the blast loads of flat plates 6 , 7 , the widely used empirical formulas were proposed by Kingery and Bulmash 8 , which were also written into design manuals 9 and numerical programs 10 , however, these empirical formulas differ significantly in the near-field blasts, which is often attributed to the variability of blast waves due to the physical mechanism for this phenomenon is not clearly understood 11 , 12 . However, the representation method of scaled distance in the empirical formula defaults to the blast waves as spherical waves, For the real scene of bomb attacks, the blast waves in near-field blasts which poses a great threat to buildings are usually non-spherical 13 , owing to the shape of charges, even spherical charges are difficult to detonate symmetrically in actual tests 14 .…”
Section: Introductionmentioning
confidence: 99%